PATERNAL PHYLOGENETIC RELATIONSHIPS BASED ON ZINC FINGER PROTEIN-Y (ZFY) GENE IN THE LAKOR GOAT BREED - KUNDA, RONY MARSYAL; KAKISINA, PIETER; RUMANTA, MAMAN; MONIHARAPON, MECHIAVEL; VOLKANDARI, SLAMET DIAH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study aims to trace the kinship of the Lakor goat breed based on Paternal Linked using the Zinc Finger Protein-Y (ZFY) region on the Y-chromosome. This study began with non-invasive sampling (hair follicles) from 64 bucks (male individuals), followed by DNA extraction. The extracted DNA molecules are used as a template for amplification of the ZFY target region, with PCR and sequencing techniques. The PCR product of each target gene is sequenced to determine its nucleotide sequence. The molecular data of the target gene resulting from sequencing and DNA sequences obtained from the international database are aligned with the Clustal W program software present in MEGA version X. Phylogenetic analysis shows that the Lakor goat breed as monophyly above 90% bootstrap homology, and two haplotypes i.e C. aegagrus haplotype zI ZFY and the other in C. hircus haplotype Y1 ZFY. These haplotypes differ only in two nucleotides in our alignment, which is site 321 (C-T), in the haplotype C. aegagrus haplotype zI ZFY, and site 512 (G-A) in C. hircus haplotype Y1 ZFY. Phylogenetic analysis indicated that C. aegagrus (bezoar) is the ancestor of the native goats in Indonesia, including the Lakor goats.